Deslocamento do trabalho feminino e os novos contornos da divisão sexual do trabalho na construção civil em Anápolis e Goiânia - Jorge, Maria Aparecida Sanches Silva (2015)
The search turns to women's work in construction, quarries functions, ceramist, tiler, rejuntadora. Focusing on the issues of women's work and the new format of the sexual division of labor, this study verifies and analyzes the women's movement of the reasons for this sector, the precariousness, intensification of domestic work delegation, the craftsmanship, polarization, education at the construction sites in Anapolis and Goiania. The research is focused on the search and verification of the new format of the sexual division of labor, to identify elements that show changes that break with inequalities or promote forms of exploitation of women's work. The objective of the study turns to the analysis of the behavior of the female labor force, on the issues of sexualization of occupations governing the sexual division of labor in the construction industry; Checks whether this shift providing further disqualification, insecurity and intensification of women's work or breaks the hierarchical system of gender in a traditionally male profession. The survey was conducted on construction sites, with interviews, observations and description of the female work everyday in the finishing sector. It was found that the displacement is promoted by male labor shortage, by professional training courses, the appeal of a formal contract, wages and these women are mostly out of domestic work and are inserted into the finishing sector, workplace exclusively manual, which "produce and clean" have the same dimension. The research revealed that work in the finishing sector has been a reclassification promoted by manual skills. Thus, it is possible to raise the presumption of likely feminization of construction finishing sector in the companies surveyed.